The Practice of Philology in the Nineteenth-Century Netherlands - Zuidervaart, Huib; van Kalmthout, Ton (History of Science and Scholarship in the Netherlands, 2015)
Dutch scholarship has played an important role in philology since the early days of Leiden University. This volume illuminates how philology and its focus on the critical examination of classical texts-a tradition that had previously exerted considerable influence across fields as diverse as theology, astronomy, law, and politics-began an accelerated process of specialization in the 1800s. As former subareas like linguistics and history branched off into independent fields with their own methodologies, philology found its authority narrowing in scope within newly defined boundaries. Providing a fresh perspective on the evolution of Dutch philology as a discipline in the humanities, this is a fascinating look at a historically vital field of thought.